Health-related quality of life in Slovenian pediatric and young adult patients with rare kidney diseases: Kakovost življenja slovenskih otrok in mladih odraslih z redkimi boleznimi ledvic - Trstenjak, Nina; Zupanc, Nastja; Marčun Varda, Nataša (Acta Medico-Biotechnica, 2025)
Purpose: Patients with rare kidney diseases require specialized and typically lifelong treatments. Quality of life is an important aspect of a person’s well-being, and it is influenced by numerous factors. This cross-sectional study aimed to assess the quality of life of affected children and young adults to guide optimal treatment and enhance care. It is based on our research paper that was awarded the Dean’s Recognition for Students on December 6, 2024.Methods: The study included patients aged 2–25 years with rare kidney diseases who were managed in the Department of Pediatrics at the University Clinical Centre Maribor and registered in the European Rare Kidney Disease Registry. The Pediatric Quality of Life Inventory questionnaire was sent to the participants and their parents as proxy reports, and 69 patient questionnaires and 58 parent questionnaires were obtained for analysis. Descriptive methods were used to present the results. The Kruskal–Wallis and Dunn’s post hoc test with Bonferroni correction were used to determine functioning differences among different age groups, whereas the paired-samples t test was used to compare parent–child responses.Results: Patients rated their overall quality of life with a median of 82.5 [interquartile range (IQR) = 17.45], whereas parents rated it with a median of 83.91 (IQR = 17.85), out of 100. Adolescents had better social functioning than young children (H = 11.335; P = 0.023). Parents’ reports aligned with those of children [physical (t = –0.354; P = 0.725), emotional (t = –0.574; P = 0.569), social (t = 0.061; p = 0.951), school (t = –0.271; P = 0.787), and total functioning (t = –0.765; P = 0.448)].Conclusion: Participants had good overall functioning, highlighting the importance of multidisciplinary care and the need for further interventions to enhance health and prevent potential deterioration.
Keywords: children; chronic kidney disease; functioning; PedsQL; quality of life; rare kidney diseases